The Feasibility Test of “COVID” Learning Strategy: An Alternative Approach to Cope Learning Process during Pandemic of COVID-19 - Sh Sugiharto; Benny Arief Setyanto (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: The COVID-19 outbreak requires spread prevention strategies that affects the education system at all levels. Consequently, appropriate and relevant learning strategies are required. The study aimed to examine the feasibility of “COVID” learning strategy as an alternative online learning system during pandemic COVID-19. Methods: The study applied a pre-experimental design with a one-group pretest-posttest approach. The sample size (34 participants) was determined using G*Power 3.1.9.7 software. The open recruitment of the participants was announced through WhatsApp. Students who were willing to be the participants were asked to fulfill the enrollment link. As the intervention, nursing students were taught using the "COVID (Creative, Outcomes-oriented, Valuable, Innovative, and Desire)" learning strategy. Two variables i.e. critical thinking and learning environment satisfaction were measured using the Diagnostic Thinking Inventory (DTI) and the Dundee Ready Education Environment Measure (DREEM), respectively. The paired t-test was used to analyze the DTI and DREEM data before and after the intervention. Results: The results show that the Flexibility Thinking dimension of DTI was significant with t-value of (30) = 7.025, p = .000. Likewise, with the assessment of the learning atmosphere using DREEM, a significant result was obtained with t (33) = -457,263, p = .000. The respondents' satisfaction with the "COVID" learning strategy was 8.5 on average. Conclusion: The "COVID" learning strategy can improve flexible thinking and student satisfaction with the online learning process. The "COVID" learning strategy can be an alternative learning strategy that is effective in the online learning process.